2013
DOI: 10.1177/1753465812472387
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for antibiotic prescribing in patients with exacerbations of COPD in general practice

Abstract: Background: The aim of this study was to describe the antibiotic prescribing rate in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD), to analyse predictors for antibiotic prescribing and to explore the influence of the use C-reactive protein (CRP) rapid test. Methods: A cross-sectional study was carried out in January and February 2008 in primary care. General practitioners (GPs) from six countries (Denmark, Sweden, Lithuania, Russia, Spain and Argentina) registered all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 24 publications
4
38
0
2
Order By: Relevance
“…Quantitative investigations on GPs’ prescribing behavior for AECOPD (and other respiratory diseases) have shown that symptoms and signs such as colored sputum, severe dyspnea, and CRP testing are associated with treatment decisions for antibiotics and/or oral corticosteroids 2932. Our findings confirm that GPs consider these clinical cues relevant to their decision-making, yet also show that GPs cannot always rely on their presence and significance.…”
Section: Discussionsupporting
confidence: 70%
“…Quantitative investigations on GPs’ prescribing behavior for AECOPD (and other respiratory diseases) have shown that symptoms and signs such as colored sputum, severe dyspnea, and CRP testing are associated with treatment decisions for antibiotics and/or oral corticosteroids 2932. Our findings confirm that GPs consider these clinical cues relevant to their decision-making, yet also show that GPs cannot always rely on their presence and significance.…”
Section: Discussionsupporting
confidence: 70%
“…A cross-sectional study showed prescribing rates of 92.9% in Russia, 81.1% in Spain, 80.6% Lithuania, and only 48.9% in Denmark 14. Since we detected pathogens in only a limited percentage of cultures, our local data suggest that the role of bacteria in AECOPD in primary care is limited.…”
Section: Discussionmentioning
confidence: 60%
“…CRP as point of care test is already feasible and in use by general practitioners in the Netherlands. The addition of CRP testing during AECOPD showed a strong reduction in antibiotic prescription in patients with AECOPD with purulent sputum, and antibiotic prescription rates were 26% lower in general practitioners using CRP tests 14. The guidelines of Norway and Denmark recommend the use of biomarkers for treatment with antibiotics of outpatients with AECOPD 20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Next, we included prescriptions for the most frequently used antibiotics in the treatment of exacerbations. 33 …”
Section: Methodsmentioning
confidence: 99%